Effect of the CaO Catalyst Concentration Based on Barnacle Shells (Tetraclita squamosa) on Biodiesel Production from Coconut Oil - Rakasiwi, Rinjani; Rezeki, Sri; Hafiza, Nurul; Ivontianti, Wivina Diah (UI Scholars Hub, 2025)
Barnacle shells are a source of the calcium oxide (CaO) catalyst, which is nontoxic, highly alkaline, and biodegradable. This study aims to determine the characteristics and the effect of the CaO catalyst concentration obtained from the calcination of barnacle shell particles at a temperature of 900 ℃ for 2 and 4 h on the transesterification reaction of biodiesel from coconut oil. Transesterification was conducted at 65℃ for 2 h with a methanol/coconut oil molar ratio of 6:1. The concentration of the CaO catalyst was varied (i.e., 1wt%, 3wt%, 5wt%, 7wt%, and 9wt%) for coconut oil. The results of the characterization of the catalyst through the X-ray diffraction test showed that the best calcination time was 4 h. The characteristic peaks of CaO appear at diffraction angles (2θ) of 31.4°, 36.0°, 54.3°, and 64.7°. The optimum catalyst concentration was 5wt%, where the highest yield (92.17%) was obtained with the following biodiesel characteristics: density at 40 ℃ of 863 kg/m3 , kinematic viscosity at 40 ℃ of 3.03 cSt, water content of 0.01%, and acid number of 0.26 mg KOH/g. The results of the gas chromatography–mass spectrometry analysis based on the optimum catalyst concentration showed that biodiesel was composed of methyl ester compounds, which were dominated by methyl laurate (54.52%) and methyl myristate (19.37%).